2013
DOI: 10.1016/j.jss.2012.02.055
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of muscle force after immediate and delayed reinnervation using nerve-muscle-endplate band grafting

Abstract: Background Because of poor functional outcomes of currently used reinnervation methods, we developed novel treatment strategy for the restoration of paralyzed muscles - the nerve-muscle-endplate band grafting (NMEG) technique. The graft was obtained from the sternohyoid (SH) muscle (donor) and implanted into the ipsilateral paralyzed sternomastoid (SM) muscle (recipient). Methods Rats were subjected to immediate or delayed (1 or 3 months) reinnervation of the experimentally paralyzed SM muscles using the NME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…Our studies [28,3033] and others [23,25,42,43] have demonstrated that force measurement is a reliable technique in determining the degree of functional recovery of a reinnervated muscle. The denervated muscle is characterized by reduced muscle mass, decreased fiber size, increased connective tissue, and reduced metabolic capacity [44,45] which can be reversed by reinnervation [28,33,46]. Muscle wet weight has been widely used to evaluate muscle reinnervation [28,3133,4749].…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Our studies [28,3033] and others [23,25,42,43] have demonstrated that force measurement is a reliable technique in determining the degree of functional recovery of a reinnervated muscle. The denervated muscle is characterized by reduced muscle mass, decreased fiber size, increased connective tissue, and reduced metabolic capacity [44,45] which can be reversed by reinnervation [28,33,46]. Muscle wet weight has been widely used to evaluate muscle reinnervation [28,3133,4749].…”
Section: Discussionmentioning
confidence: 83%
“…Muscle force measurement is widely used to assess the mechanical function and contractile properties of a muscle [3541]. Our studies [28,3033] and others [23,25,42,43] have demonstrated that force measurement is a reliable technique in determining the degree of functional recovery of a reinnervated muscle. The denervated muscle is characterized by reduced muscle mass, decreased fiber size, increased connective tissue, and reduced metabolic capacity [44,45] which can be reversed by reinnervation [28,33,46].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations